Balancing learning and enjoyment in serious games: Kerbal Space Program and the communication mediation model - ROSENTHAL, Sonny (Institutional Knowledge at Singapore Management University, 2022)
When designed well, serious games can support effective learning. This study used the communication mediation model to examine the process and outcomes of playing serious games, in this case, the science-themed game, Kerbal Space Program. During a 4-h research session, 241 undergraduate students played through the game's tutorial missions and completed surveys to measure variables of interest. Results of structural equation modeling showed that game progress was positively related to self-efficacy in computer gaming (β = 0.26) and ordinary science intelligence (β = 0.13). Knowledge acquisition was positively related to game progress (β = 0.21) and positively predicted experiential attitude (β = 0.35) and instrumental attitude (β = 0.35) toward the game. Finally, gaming continuance intention was positively related to experiential attitude (β = 0.68). In addition to those direct effects, there were several indirect effects consistent with the communication mediation model. These findings echo past scholarship on balancing the serious side and the gaming side of serious games but emphasize player traits and other psychological factors of the gaming experience.